The Analysis of the Effect of Remuneration Through Employees' Performance Improvement at Discovery Hotel Ancol - Lieansyah, Fernando; Iskandar, Hari (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2023)
The issue of remuneration in Jakarta is widely acknowledged, particularly the provincial minimum wage, which some workers find insufficient to meet their families' needs due to the high cost of living. In light of this situation, this research aims to examine whether remuneration serves as a motivating factor for employees at Discovery Hotel Ancol to enhance their performance. Employing a quantitative approach, this study utilizes statistical analysis as a means of data measurement, employing questionnaires distributed to 175 eligible respondents who are permanent employees receiving complete remuneration at Discovery Hotel Ancol. Saturation sampling is utilized as the sampling method for this study. Secondary data for this research are acquired from previous studies, books, journals, and the internet. The t-test conducted in this study reveals a significant influence of remuneration on employee performance at Discovery Hotel Ancol. The calculated t-value of 5.5958 surpasses the t-table value of 1.973, leading to the acceptance of the null hypothesis (Ho), indicating that the remuneration provided indeed affects employee performance. The absence of multicollinearity is supported by tolerance values above 0.10 and VIF values below 10. Heteroskedasticity test results demonstrate a significance value of 0.134, which exceeds 0.05, thereby concluding that the data utilized in this study does not exhibit heteroskedasticity. Furthermore, the R2 value of 0.413 indicates that the remuneration variable accounts for 41.3% of the influence on employee performance, with the remaining 58.7% being attributed to other unexplored variables. The findings confirm that the remuneration variable significantly affects employee performance at Discovery Hotel Ancol. It is hoped that this research will benefit stakeholders such as hotel owners and academics.